A New Caputo Fractional Differential Equation with Infinite-Point Boundary Conditions: Positive Solutions - Jing Ren; Zijuan Du; Chengbo Zhai (Fractal and Fractional)
This paper mainly studies a different infinite-point Caputo fractional differential equation, whose nonlinear term may be singular. Under some conditions, we first use spectral analysis and fixed-point index theorem to explore the existence of positive solutions of the equation, and then use Banach fixed-point theorem to prove the uniqueness of positive solutions. Finally, an interesting example is used to explain the main result.